Influência dos parâmetros e modelos de linhas na solução do fluxo de carga de sistemas de distribuição de energia elétrica - Montemezzo, João Felipe (2016)
Distribution Systems traditionally operate radially and having little information about the operating status of the network, which is estimated by the results of the load flow. The network is formed by multiphase feeders with untransposed lines, which must be added the inclusion of distributed generation, and in some cases, feeders with great extension, resulting in high level of load imbalance. That it must be added the tendency of having to operate the distribution systems more actively and efficiently, considering the greater penetration of distributed generation, storage systems and demand response. It results in the need for reliable tools for operation and planning. Among these tools the load flow is the most used and therefore deserves special attention. However, given the diverse operating conditions, it is necessary that components get modeled appropriately for reliable results. In this context, this work gathers the main mathematical models that can be used to represent lines of distribution systems, and evaluates how they influence the results obtained with load flow. Overhead and underground lines are considered, considering different topological arrangements and loading, for both primary and secondary networks. Moreover, the differences are investigated in the load flow solution considering the conventional and compact networks. Based on the assessments made in the work it is concluded that, due to the topology of distribution systems, the lines can be well represented by the short line model, with self and mutual impedances calculated by modified Carson equations. And the use of compact networks results in lower voltage drops and unbalance between the phases, due to the increased proximity and symmetry between conductors.